Physics benchmarks of the VELO upgrade. (22nd December 2016) - Eklund, L.
Abstract: The LHCb Experiment at the LHC is successfully performing precision measurements primarily in the area of flavour physics. The collaboration is preparing an upgrade that will start taking data in 2021 with a trigger-less readout at five times the current luminosity. The vertex locator has been crucial in the success of the experiment and will continue to be so for the upgrade. It will be replaced by a hybrid pixel detector and this paper discusses the performance benchmarks of the upgraded detector. Despite the challenging experimental environment, the vertex locator will maintain or improve upon its benchmark figures compared to the current detector. Finally the long term plans for LHCb, beyond those of the upgrade currently in preparation, are discussed.